Ethical Governance in School Public Relations: Managing Stakeholder Relationships in Secondary Education - Disa Sri Ilma Aditya; Andri Ani Suryawijaya; Herry Kiswanto; Renny Yuliarti; Riska Meisyi Putri; Mardalena Mardalena; Anggia Pratiwi (Universitas Nurul Jadid Probolinggo, Indonesia, 2026)
This study aims to examine the implementation of public relations ethics in managing relationships between educational institutions and their stakeholders and to explore its contribution to institutional reputation and stakeholder trust. The research employed a qualitative case study approach to obtain an in-depth understanding of ethical public relations practices within a school setting. Data were collected through semi-structured interviews, direct observations, and document analysis, and were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that ethical public relations practices are demonstrated through transparent information dissemination, responsive and two-way communication, respect for stakeholder feedback, and accountability in decision-making processes. These practices strengthen collaboration between schools, parents, and the wider community while fostering a positive institutional image and increasing public confidence. Nevertheless, the study also identifies challenges related to maintaining ethical communication in digital environments, where rapid information exchange requires consistency, accuracy, and professional responsibility. The findings imply that strengthening ethical public relations practices can enhance stakeholder engagement, institutional credibility, and sustainable communication strategies in educational institutions amid ongoing digital transformation.